Thrombolysis at 3-4.5 hours after acute ischemic stroke onset--evidence from the Canadian Alteplase for Stroke Effectiveness Study (CASES) registry. - Shobha, N; Buchan, A; Hill, MD (2011)
BACKGROUND: Extending the therapeutic window for thrombolysis is an important strategy in maximizing the proportion of patients treated. ECASS III examined a 3-4.5-hour window and showed a benefit to treated patients. We examined the experience in Canadian centres using intravenous tPA treatment in the 3-4.5-hour time window. METHODS: The data were obtained from the CASES (Canadian Alteplase for Stroke Effectiveness Study)--a prospective, multicentric cohort study with patient enrollment from 60 centres across Canada over 2.5 years. The 90-day outcome, mortality and symptomatic intracranial hemorrhage of patients thrombolysed between 3 and 4.5 h and within 3 h of symptom onset were compared. A mRS 0-1 (no symptoms at all or no significant disability despite symptoms, able to carry out all usual duties and activities) at 90 days was defined as a favorable outcome. RESULTS: A total of 1,112 patients with complete data were included. 129 (11.6%) patients received tPA between 3 and 4.5 h of symptom onset and 983 (88.4%) patients received tPA within 3 h. At 90 days, 39.4% of the patients in the 3-4.5-hour treatment group and 36.5% of patients in the under 3-hour treatment group attained a mRS ≤1. There were no differences between the two groups regarding their functional status at 3 months. There was a trend towards higher rate of sICH in the 3-4.5-hour group compared to the 0-3-hour group (7.8 vs. 3.8%, p = 0.06). Similarly there was a trend towards higher rate of deaths in the 3-4.5-hour group compared to the 0-3-hour group (28.4 vs. 21.4%, p = 0.09). A χ(2) test for trend demonstrated a rising proportion of symptomatic ICH in later time windows (p = 0.013). A similar trend (non-significant) was observed for mortality. CONCLUSION: Our study suggests that patients with acute ischemic stroke may be successfully treated with intravenous tPA in the 3-4.5-hour treatment window, but cautions that later time window treatment may result in greater adverse events.